Drinking alcohol as harmful habits among young people - Miljanović G.; Stanić G.; Stojanović G.; Terzić N.; Janošević M. (Association of Nurses Technicians and Midwives, 2015)
Background: The consumption of alcohol is a massive and almost pandemic occurrence behavior, in general, and the youth population and becomes part of the social pathology, with the inevitable health consequences. Objective: To determine the habits of alcohol consumption in the population of students, to determine their attitudes toward alcohol consumption and awareness of the damaging effects of alcohol consumption. Methodology: descriptive and observational method - household survey, a survey was conducted in the student population, the Medical College of Professional Studies in Belgrade, on a random sample of N-316 at all years of basic professional studies. We used part of the ESPAD questionnaire that is tailored to the needs of this research is anonymous and consisted of 14 questions. Results: The results indicate that 92.4% of respondents have experience of drinking alcohol. Half of the first alcoholic drink consumed at the urging of other /friends. The motives of alcohol consumption are generally hedonistic nature. The results indicate that 69.3% of respondents have experience of drinking. The subjects consumed approximately all kinds of alcohol, and more than half of the respondents consumed alcohol in the company of a friend, 56.3% of them. More than half of respondents, 56% have a positive attitude towards the consumption of alcohol, while only 33% of students are well informed about the harmful effects of alcohol consumption. Discussion: The consumption of alcohol is the most common form of addiction among young people. Motiva and trigger a more in addition to the influence of peers there is a curiosity and benevolent treatment of our society towards alcohol drinking. Peers act as an influential model, the introduction of the high-risk activities. Freshman population is particularly at risk. Conclusion: The respondents were largely consumed alcohol. Bearing in mind that the testing was anonymous and the profession for which the educated respondents, the results are certainly worse in both subjects and the general population of students. It is therefore very important in the course of their training, raising awareness about the dangers of alcohol consumption and the development of skills, so that young people learn how to resist pressures to adopt new forms of harmful behavior, including drinking alcohol.